Ecosystem services potential and soil conservation policies with emphasis on degraded pastures in Brazil - da Costa, Adriana Monteiro [UNESP]; de Moura, Maise Soares; Navarro, Isadora Fonseca; da Silva, Victor Cordeiro; Pissarra, Teresa Cristina Tarlé [UNESP]; Valera, Carlos Alberto [UNESP]; Fernandes, Luís Filipe Sanches [UNESP]; Pacheco, Fernando Antonio Leal [UNESP] (Elsevier, 2024)
Different global agendas have discussed the role of soils in mitigating and reducing global problems related to climate change, food security, biodiversity and erosion, among others. With this in mind, the aim was to draw up an overview of the main soil agendas in Europe and Brazil, analysing their impact on the establishment of legal frameworks for soil use and conservation. In Brazil, pastures are seen as an important alternative for converting degraded areas into ecosystem services. To this end, a literature review was carried out using databases on the Scopus, Web of Science, Science Direct and Scielo platforms, as well as consulting documents from the European Union Missions in Horizon Europe and Brazilian legislation on the subject. In a pilot river basin, the Potential for Conservation Use (PCU) method was applied, which is used in Brazil to assess the impacts of different uses on the natural capital of soils, serving as a metric to guide public soil conservation policies. It was concluded that, on the European scene, discussions on soils have taken place in an integrated and organised way, with actions to mobilise different players in society. In Brazil, even though there are important legal frameworks, actions are still restricted and disjointed, pointing to the need for progress in soil governance. In both scenarios, there is a need for scientifically validated metrics at regional scales that can contribute to a harmonised database capable of subsidising the development of efficient public policies to advance soil conservation at a global level.
Keywords: Conservation use potential; EU mission; PronaSolos; Soil governance; Soil services